The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/molecules28062733
|View full text |Cite
|
Sign up to set email alerts
|

Recent Development of Rhenium-Based Materials in the Application of Diagnosis and Tumor Therapy

Abstract: Rhenium (Re) is widely used in the diagnosis and treatment of cancer due to its unique physical and chemical properties. Re has more valence electrons in its outer shell, allowing it to exist in a variety of oxidation states and to form different geometric configurations with many different ligands. The luminescence properties, lipophilicity, and cytotoxicity of complexes can be adjusted by changing the ligand of Re. This article mainly reviews the development of radionuclide 188Re in radiotherapy and some inn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 142 publications
(183 reference statements)
0
16
0
1
Order By: Relevance
“…26−29 stability and endow them with better functions than their components while preserving their original characteristics, resulting in a synergistic enhancement effect. 21,25,39,30 GSH is an antioxidant that can scavenge ROS and protect cells from oxidative damage. 21 However, the overexpression of GSH in the TME can quench the ROS generated by catalytic reactions, compromising the efficacy of catalytic therapy.…”
Section: Introductionmentioning
confidence: 99%
“…26−29 stability and endow them with better functions than their components while preserving their original characteristics, resulting in a synergistic enhancement effect. 21,25,39,30 GSH is an antioxidant that can scavenge ROS and protect cells from oxidative damage. 21 However, the overexpression of GSH in the TME can quench the ROS generated by catalytic reactions, compromising the efficacy of catalytic therapy.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12] Rhenium(I) tricarbonyl complexes were found to be potential chemotherapeutic agents against cancer many years ago, several compounds have demonstrated cytotoxicity that matches or surpasses that of cisplatin, a clinically used anticancer drug. [13][14][15][16][17] In addition, Re(I) tricarbonyl complexes were found to be efficient PDT PSs. [18][19] For these reasons, the combination of a Ru(II) polypyridyl complex and a Re(I) tricarbonyl complex in a single molecule would be beneficial for the design of a PDT PS as it would give a high probability for ISC.…”
Section: Introductionmentioning
confidence: 99%
“…Rhenium(I) tricarbonyl complexes were found to be potential chemotherapeutic agents against cancer many years ago, several compounds have demonstrated cytotoxicity that matches or surpasses that of cisplatin, a clinically used anti‐cancer drug [13–17] . In addition, Re(I) tricarbonyl complexes were found to be efficient PDT PSs [18–19] .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that polymeric matrices, fabricated by electrospinning/electrospraying techniques, present structural and functional benefits for encapsulation of bioactive ingredients for food, pharmaceutical and medical applications or even environmental applications 17,21‐27 …”
Section: Introductionmentioning
confidence: 99%
“…(2022) 28 . Also, for pharmaceutical and medical applications electrohydrodynamic techniques have an important role, for example in electrospun nanofibrous carriers for drug release or tumor therapy 17,27,34 . For example, co‐electrospun/electrosprayed PVA/folic acid nanofibers for transdermal drug delivery were prepared, characterized, and studied in terms of in vitro cytocompatibility by Parın et al .…”
Section: Introductionmentioning
confidence: 99%